MP36: Safety and clinically important events in PCP-initiated STEMI bypass in Ottawa: a health record review. (15th May 2017) - Mitchell, S.; Dionne, R.; Maloney, J.; Austin, M.A.; Mok, G.; Sinclair, J.E.; Cox, C.; Le May, M.; Vaillancourt, C.
Abstract : Introduction: In Ottawa, STEMI patients are transported directly to percutaneous coronary intervention (PCI) by advanced care paramedics (ACPs), primary care paramedics (PCPs), or transferred from PCP to ACP crew (ACP-intercept). PCPs have a limited skill set to address complications during transport.The objective of this study was to determine what clinically important events (CIEs) occurred in STEMI patients transported for primary PCI via a PCP crew, and what proportion of such events could only be treated by ACP protocols.Methods: We conducted a health record review of STEMI patients transported for primary PCI from Jan 1, 2011-Dec 21, 2015. Ottawa has a single PCI center and its EMS system employs both PCP and ACP paramedics. We identifiedc onsecutive STEMI bypass patients transported by PCP-only and ACP-intercept using the dispatch database. A data extraction form was piloted and used to extract patient demographics, transport times, and primary outcomes: CIEs and interventions performed during transport, and secondary outcomes: hospital diagnosis, and mortality. CIEs were reviewed by two investigators to determine if they would be treated differently by ACP protocols. We present descriptive statistics.Results: We identified 967 STEMI bypass cases among which 214 (118 PCP-only and 96 ACP-intercept) met all inclusion criteria. Characteristics were: mean age 61.4 years, 78% male, 31.8% anterior and 44.4% inferior infarcts, mean response time 6 min, total paramedic contact time 29 min, and in cases of ACP-intercept 7 min of PCP-only contact time.A CIE occurred in 127 (59%) of cases: SBP<90 mmHg 26.2%, HR<60 30.4%, HR>100 20.6%, malignant arrhythmias 7.5%, altered mental status 6.5%, airway intervention 2.3%, 2 patients (0.9%) arrested, both survived. Of the CIE identified, 54 (42.5%) could be addressed differently by ACP vs PCP protocols (25.2% of total cases). The majority related to fluid boluses for hypotension (44 cases; 35% of CIE). ACP intervention for CIEs within the ACP intercept group was 51.6%. There were 6 in-hospital deaths (2.8%) with no difference in transport crew type.Conclusion: CIEs are common in STEMI bypass patients however a smaller proportion of such CIE would be addressed differently by ACP protocols compared to PCP protocols. The vast majority of CIE appeared to be transient and of limited clinical significance.